(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
The Refusal of Blood Transfusions by Jehovah’s Witnesses in Light of the Latest Ruling from the European Court of Human RightsThe contribution explores the issues related to the right to religious freedom and the self-determination of Jehovah’s Witnesses, particularly in connection with their refusal of blood transfusions for reasons of faith. This complex legaland bioethical issue becomes particularly pressing when the patient’s refusal of treatment could lead to fatal consequences, necessitating a delicate balance between individual autonomy, religious freedom, and the State’s duty to protect life and public health. The contribution also analyzes how the recent European Court of Human Rights ruling in Pindo Mulla v. Spain clarifies, although with some limitations, the intricate relationship between personal religious beliefs and the legal obligations of healthcare professionals. It offers an interpretation that reflects the profound tensions present in contemporary pluralistic societies, where religious beliefs, ethical values, and legal duties can collide in complex ways.